THE INFLUENCING FACTORS ON MODES CHOICE BETWEEN TRAIN AND MOTORCYCLE OF COMMUTER IN SOLO-YOGYAKARTA TRIP - Oktavia Sulistya Putri, Andina
The increased movement between urban metropolitan Solo and Yogyakarta caused by daily movement of commuter workers. The use of private vehicles as a mode of commuting causes negative impacts such as air pollution and traffic congestion. The Solo-Yogyakarta commuter trains become one of the alternatives of sustainable mode with low fuel consumption just about 0.002 liters/km/passenger. Nevertheless, although the government has enacted policies to increase the number of train passengers, this mode has not yet become the major mode for commuter workers. This study aims to identify factors affecting commuting workers in choosing a working mode between train and motorcycle, and to predict the amount of time and travel costs that may affect the probability of commuting to choose using train as a working mode. Respondents were selected through multistage sampling with a total of 138 respondents. The probability modeling is performed using a binary logit model to modeling the probability of selecting modes between train and motorcycle. Software used for parameter estimation is SPSS and NLOGIT. The results showed that there were eight factors influencing modes choice based on correlation analysis with Chi Square Test, Mann Whitny-U Test, and Binary Logit Regression. The eight factors are gender, SIM ownership, the use of public transport to the station as feeder, departure schedules, frequency of weekly usage, distance from home to work, travel time, and travel cost. Commuters are more likely travel with motorcycle than train. This is known based on the calculation of utility value which known that the average utility value of motorcycle usage is higher than the average utility value of commuter train usage. The probability of choosing motorcycle by commuter is bigger than the train (71.19% versus 18.81%). In the existing conditions, it is known that the average travel time and the travel cost by train are 63.9 minutes and Rp. 20365,32. Based on the model sensitivity analysis, it is predict that commuters will be willing to use train as a commuter mode when the time and travel cost by train are lowered to 43 minutes and Rp. 12.265,32. While based on the results of willingness to pay analysis known that the amount of travel expenses that will be paid by the commuter to use train as a commuter mode is RP.14.000,00. So, it can be seen that there is a possibility to make commuter train as the main mode of working trip by enhance the transportation mode service. Some of recommendations that suggested are applying train schedules according iv to user requirements, improving public transport services as feeder, providing disincentives on commuter trips using motorcycles, shortening total travel time by train, and minimize the total travel cost by train.